Tinjauan Filsafat Hukum Islam terhadap Sanksi Pidana Delik Kondermoord Pasal 342 KUHP - Latifah, Nani (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2018)
The article discusses a review of Islamic legal philosophy towards offense sanctions in the form of the Article 342 of the Criminal Code